Reponse of Different Combinations of Manure and Fertilizers to the Yield of Rape Crop - Baliyan, SP; Baliyan, PS; Rao, KS Madhava (International Journal of Agricultural Research, Innovation and Technology, 2013)
This study was an attempt to determine the effect of different combinations of manure and fertilizers on the yield of rape crop so as to improve yield by recommending the best combination of manure and fertilizers to the rape growers in Botswana. Rape crop was planted on farmers field in a complete randomized block design where nine different combinations of manure and fertilizers, namely, chicken manure (Ch); Ch and NPK (2:3:2); Ch and Fe (Iron); Ch, NPK and Fe; Ch and Urea; Ch, NPK and Urea; Ch, Urea and Fe; Ch, NPK, Urea and Fe; and control (No application of manure and fertilizer) were considered. Each fertilizer combination was replicated four times in a total of thirty six plots in the layout of the experiment. The data on rape yield was collected. The leaves of rape were harvested three times a month and the rape yield (in kg) was recorded in a harvest sheet. A two way analysis of variance (ANOVA) was performed using the SPSS software. The results indicated that fertilizer combination of chicken manure, NPK and Urea produced the highest yield of rape which was 2.61 times higher than the yield produced by the control plots (where no manure and fertilizer was applied) and therefore, a fertilizer combination of chicken manure, NPK and Urea was recommended to the rape growers. Suggested future studies included the comparative profitability of different fertilizer combinations as well as the effects of different doses of the organic and inorganic fertilizers on rape production. DOI: http://dx.doi.org/10.3329/ijarit.v2i2.14013 Int. J. Agril. Res. Innov. & Tech. 2 (2): 44-47, December, 2012